Dinamika Perubahan Iklim dan Keberlanjutan Produksi Kopi: Analisis Spasial Stok Karbon: Dynamics of Climate Changes and Suistainability of Coffee Production: Spatial Analysis of Carbon Stocks - Abdullah, Nuryahya; Maryana, Dwi; Kalsum, Ummu (Jurnal Ecosolum, 2024)
Climate change threatens the sustainability of coffee production in Indonesia. One of the causes of climate change is the reduction in carbon stocks. Coffee stands have a big role in maintaining carbon stocks. Carbon stocks are part of the global carbon cycle. This research aims to create a carbon stock distribution map on coffee fields in Gowa Regency. This research uses a spatial analysis method which is integrated with the results of soil analysis using the Walkey and Black method to determine the carbon content in the soil which produces a Carbon Stock Distribution Map in Gowa Regency. The research results explained that the highest carbon content was 2,85% in Tanete Village, Tombolopao District (TB2) with a production of 2 kg per tree. This is because the existence of coffee stands in these two regions is still maintained. The carbon content in Pattapang Village, Tinggi Moncong District (TM3) shows the lowest percentage of organic carbon content at 0,82% with a plant age of >10 years and a production of 0,5 kg per tree. Horticultural farming and the massive change in use of agricultural land into villas/settlements is one of the main causes. This also happened in Bungaya and Bonto Lempangan sub-districts. It is hoped that there will be guidelines for adaptation to climate change that include coffee insurance scheme strategies to balance climate risks, diversified multi-strata shelter management to manage seasonal rainfall variability and extreme temperatures, and institutional strengthening, namely community organizations to face increasing market risks related to the resilience of coffee production.